(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
One of the most important tasks of the modernizing country of Uzbekistan is to create a system of educating and effectively using a new generation of young, innovative-minded, enterprising and patriotic people in public administration and its structures (ministries, governments, enterprises, organizations, etc.). Because the independence of the state, the development of society depends on the professional knowledge and skills of specialists living in this country, working in various sectors of the economy.